Exploring and preserving old apple cultivars of the Carpathian basin - Tóth, M. (International Journal of Horticultural Science, 2005)
In a few scattered orchards of the Carpathian basin one can still find our most common historical apple cultivars and certain traces of traditional cultivation. We consider it an important part of the Department's breeding work to explore old apple cultivars which can be used as parent partners and sources of resistance, to identify them pomologically as well as to examine the production and marketing value of old cultivars recommended for cultivation in ecological production and in gardens. This paper documents the results of expedition and collecting work carried out in three regions of the Carpathian basin (foot of the Carpathian Mountains, Transylvania, Aggtelek karst area), and also the saving of old Hungarian apple cultivars preserved until present in the English National Fruit Collection. A total of more than 100 old apple cultivars and variations, as well as 13 valuable genotypes were collected during our explorations in the above mentioned four areas. A further aim of our work is to contribute to the protection of still savable archaic fruit production relict= areas and to the preservation of cultivars in the certain regions, and also to promote the recognition of the aesthetic landscape value of old apple trees and endemic orchards of old cultivars. Our good co-operating partners in this work are Aggtelek National Park, Farmer Club of Visk and the consultation centre of Hungarian horticulturist training beyond the border in Nyárádszereda.